2013
DOI: 10.1371/journal.pone.0067377
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Analysis of the Pine Wood Nematode Bursaphelenchus xylophilus Reveals the Tangled Roots of Parasitism and Its Potential for Molecular Mimicry

Abstract: Since it was first introduced into Asia from North America in the early 20th century, the pine wood nematode Bursaphelenchus xylophilus has caused the devastating forest disease called pine wilt. The emerging pathogen spread to parts of Europe and has since been found as the causal agent of pine wilt disease in Portugal and Spain. In 2011, the entire genome sequence of B. xylophilus was determined, and it allowed us to perform a more detailed analysis of B. xylophilus parasitism. Here, we identified 1,515 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 74 publications
5
125
0
Order By: Relevance
“…Additionally, enrichment in peptidase inhibitors were also found in increased proteins of B. xylophilus secretome and previous studies on B. xylophilus secretome20 indicated that the number of secreted peptidase inhibitors in B. xylophilus was significantly greater than in other parasitic nematodes. Peptidases are known to play essential roles against pathogens in plant defence system27 and overexpression of peptidase genes in the host tree is considered one of the most intense reactions in the case B. xylophilus infection28.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Additionally, enrichment in peptidase inhibitors were also found in increased proteins of B. xylophilus secretome and previous studies on B. xylophilus secretome20 indicated that the number of secreted peptidase inhibitors in B. xylophilus was significantly greater than in other parasitic nematodes. Peptidases are known to play essential roles against pathogens in plant defence system27 and overexpression of peptidase genes in the host tree is considered one of the most intense reactions in the case B. xylophilus infection28.…”
Section: Discussionsupporting
confidence: 69%
“…No other quantitative proteomic study involving these two species has been presented before. A comparison of secretome profiles of the plant parasitic nematodes B. xylophilus and Meloidogyne incognita has been previously described and the analysis of GO terms distribution indicated an expansion of peptidases and peptidase inhibitors in B. xylophilus secretome20. The similar comparative functional analysis of B. xylophilus and B. mucronatus secretomes, here presented, also revealed a small expansion in peptidases in B. xylophilus secretome, nevertheless it was the quantitative analysis of B. xylophilus and B. mucronatus secretomes that showed significant differences in protein abundances in both secretomes, pointing out groups of proteins possibly responsible for the main differences between these two species pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the death of the plant cells, the nematode feeds on fungal growth [79]. Due to this special feeding habit, ES products of the parasite include cell-wall-degrading enzymes like cellulases, pectate lyase, expansin-like, and venom allergen-like proteins.…”
Section: Proteins Found In the Secretome Of Parasitic Helminthsmentioning
confidence: 99%
“…The stylet is a protrusible, hollow puncturing device, that is used to penetrate plant cell walls. Figure courtesy of Shinya et al (2013) within a lineage. Most, but not all, economically high impact plant parasites such a root knot, cyst and lesion nematodes belong to the most distal nematode clade (Clade 12; Holterman et al Mol Biol Evol 23:1792-1800.…”
mentioning
confidence: 99%